Editorial (Res Medica, 2014)
The Society’s image has subtly changed in Edinburgh. In other parts we are held in the same regard, but students here look at us with different eyes.  We are rich now, amazingly so for a student society. We have exchanged a pared of our tradition and history, the work of 50 generations of past members, for hard cash. Our books for money.  The tangible for the tangible and the intangible for the tangible.The Society has not yet realised what kind of bargain it has made. It has not been able to adjust its thinking to this new state of its affairs. Like the man in the street who suddenly wins a lot of money we do not know what to do with it. A large proportion, of course, must be set aside for the building of our new and much needed premises, but after this deduction, the Society still remains possessed of a considerable sum.  The last editorial on this page spoke about the Society’s position “ at the crossroads” of the future. We are still dithering indecisively in the middle of the road.